Loss of Rat Glomerular ATP Diphosphohydrolase Activity during Reperfusion Injury Is Associated with Oxidative Stress Reactions - Candinas, Daniel; Koyamada, Nozomi; Miyatake, Tsukasa; Siegel, Jonathan; Hancock, Wayne W; Bach, Fritz H; Robson, Simon C (Thrombosis and Haemostasis, 1996)
Endothelial cell ATP diphosphohydrolases or ATPDases degrade extracellular inflammatory mediators ATP and ADP, thus inhibiting the formation of platelet thrombi, but the modulation of these ecto-enzymes during vascular injury remains largely undetermined. Renal glomerular ATPDase levels were determined in the rat following ische-mia-reperfusion or systemic complement activation, by direct biochemical methods and histochemistry. Ischemia followed by reperfusion times over 30 min were associated with loss of glomerular ATPDase activity. Cobra Venom Factor (CVF) inhibited ATPDase activity and potentiated the deleterious effects of reperfusion. Treatment with either soluble complement receptor type 1 (sCRl), an inhibitor of complement activation, or antioxidants prior to the ischemia-reperfusion was largely protective. Expression of rat glomerular ATPDase activity appears susceptible to the inflammatory injury associated with systemic complement activation and ischemia/reperfusion processes. Oxidative stress could, at least in part, result in the loss of ATPDase activity and thus thrombotic consequences of vascular injury.